The Potency of Bixa orellana Seedcouts Extract’s as Antiimflamation Drug - Hussaana, Atina; Suparmi, Suparmi (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2012)
Background: Bixin is an orange-yellow carotenoid derived from the outer seed coats of annatto (Bixa orellana L.), which antioxidant activity. However, the use of this colorant in drug potency as antiimflamatory have been explored yet. The effect of crude extract from the outer seed coats of annatto on the inflammatory was investigated to determine its antiimflamation potency.Design and Method: This study was post test only control group design. Twenty four mice is selected randomly then divided into four groups, KI (extract 0.09 mg), K.II (extract 0.18 mg dose), K.III (aspirin 90 mg), and K.IV (CMCNa 0.125%). Oedema volume was measured before injection karagenin 1%, two, 2.5, three and four hours after injection karagenin. The mean reduction in inflammation were tested by one way anova and pos hoc LSD. Result: Greatest reduction in inflammation indicated by K.III (0.100 ml), then in K.II (0.067 ml), KI (0.072 ml), and lowest in K.IV (-0.017 ml). Differences in the reduction of inflammation significantly different between KI and K.II K.IV; and K.III whereas no significant difference was found between KI and K.III K.II.Conclusion: The extract of the outer seed coats of annatto (Bixa orellana L.) have antiimflamantory activity in mice that was induced by karagenin 1% (Sains Medika, 4(2):134-141).